Endovascular Management vs Intravenous Thrombolysis for Acute Stroke Secondary to Carotid Artery Dissection: Local Experience and Systematic Review. Issue 5 (May 2016) - Haussen, Diogo C.; Jadhav, Ashutosh; Jovin, Tudor; Grossberg, Jonathan A.; Grigoryan, Mikayel; Nahab, Fadi; Obideen, Mahmoud; Lima, Andrey; Aghaebrahim, Amin; Gulati, Deepak; Nogueira, Raul G.
Abstract : BACKGROUND: Little is known regarding the endovascular management of acute ischemic stroke (AIS) related to carotid artery dissection (CAD). OBJECTIVE: To report our interventional experience in AIS from CAD and to compare it with conservative treatment of CAD with intravenous thrombolysis (IVT) via systematic review. METHODS: Retrospective analysis of consecutive high-grade steno-occlusive CAD with National Institutes of Health Stroke Scale (NIHSS) >5 and ⩽12 hours of last seen normal from 2 tertiary centers. A systematic review for studies on IVT in the setting of CAD via PubMed was performed for comparison. RESULTS: Of 1112 patients treated with endovascular interventions within the study period, 21 met the inclusion criteria. Mean age was 52.0 ± 10.9 years, 76% were male, NIHSS was 17.4 ± 5.8, 52% received IVT before intervention, and 90% had tandem occlusions. Mean time from last-known-normal to puncture was 4.8 ± 2.1 hours and procedure length 1.8 ± 1.0 hours. Stents were used in 52% of cases, and reperfusion (modified Treatment in Cerebral Ischemia 2b-3) achieved in 95%. No parenchymal hemorrhages were observed and 71% achieved good outcome (90-day modified Rankin Scale 0-2). The literature review identified 8 studies concerning thrombolysis in the CAD setting fitting inclusion criteria (n = 133). Our endovascular experience compared with the pooled IVT reports indicated that, despite presenting with higher NIHSS (17 vs 14; P = .04) and experiencing a longer time to definitive therapy (287 vs 162 minutes; P < .01), patients treated intra-arterially had similar rates of symptomatic cerebral/European Cooperative Acute Stroke Study-parenchymal hematoma 2 hemorrhage (0% vs 6%; P = .43) and good outcomes (71% vs 52%; P = .05). CONCLUSION: Our study provides evidence that the endovascular management of AIS in the setting of CAD is a feasible, safe, and promising strategy. ABBREVIATIONS: AIS, acute ischemic stroke ASPECTS, Alberta Stroke Program Early CT Score CAD, carotid artery dissection IAT, intra-arterial therapy ICA, internal carotid artery IVT, intravenous thrombolysis mRS, modified Rankin Scale mTICI, modified Treatment in Cerebral Ischemia NIHSS, National Institutes of Health Stroke Scale PH, parenchymal hematoma Abstract : Supplemental Digital Content is available in the text.